Overseers of Upper Egypt in the Old to Middle Kingdoms: Part 2 – Dossiers - Borvarski, Edward (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
The first part of this article was published in the second fascicule of ZÄS 140 (2013). The present part contains the documentation that backs up the conclusions reached in Part 1.